Metaphor and Musical Thought - Spitzer, Michael (Chicago, IL University of Chicago Press, 2003)
The experience of music is an abstract and elusive one, enough so that we're often forced to describe it using analogies to other forms and sensations: we say that music moves or rises like a physical form; that it contains the imagery of paintings or the grammar of language. In these and countless other ways, our discussions of music take the form of metaphor, attempting to describe music's abstractions by referencing more concrete and familiar experiences.Michael Spitzer's Metaphor and Musical Thought uses this process to create a unique and insightful history of our relationship with music?the first ever book-length study of musical metaphor in any language. Treating issues of language, aesthetics, semiotics, and cognition, Spitzer offers an evaluation, a comprehensive history, and an original theory of the ways our cultural values have informed the metaphors we use to address music. And as he brings these discussions to bear on specific works of music and follows them through current debates on how music's meaning might be considered, what emerges is a clear and engaging guide to both the philosophy of musical thought and the history of musical analysis, from the seventeenth century to the present day. Spitzer writes engagingly for students of philosophy and aesthetics, as well as for music theorists and historian
Keywords: Music philosophy and esthetics